2009
DOI: 10.1111/j.1540-8191.2009.00850.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Hemangioma of the Left Atrial Appendag: A Case Report and Discussion

Abstract: Cardiac hemangioma is an extremely rare, benign vascular tumor of the heart. In contrast to myxoma, hemangioma rarely involves left atrial tissue in adults and little information about the tumor is available. We encountered a 65-year-old woman with a left atrial hemangioma arising in the appendage and growing like an extracardiac mass. The tumor was removed from the left atrium with all the left appendage under cardiopulmonary bypass. Histopathological examination revealed that it was a cavernous-type hemangio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Cardiac hemangiomas rarely involves the left atrium and has been described in the LAA in few cases. 5 In few other cases, inverted LAA was described as a mass mimicking a left atrial tumor or thrombus. 6 Cardiac magnetic resonance imaging (MRI) is important to well delineate and characterize cardiac tissue and masses.…”
Section: Commentmentioning
confidence: 99%
“…Cardiac hemangiomas rarely involves the left atrium and has been described in the LAA in few cases. 5 In few other cases, inverted LAA was described as a mass mimicking a left atrial tumor or thrombus. 6 Cardiac magnetic resonance imaging (MRI) is important to well delineate and characterize cardiac tissue and masses.…”
Section: Commentmentioning
confidence: 99%
“…However, most CHs are in the ventricle, especially in the lateral wall of the LV (6). A CH rooted in the left atrial appendage is particularly rare, and only several cases have been identified in previous studies (Table 1) (7)(8)(9)(10)(11)(12)(13)(14). As a result, our case can be added to this body of literature.…”
Section: Clinical Featuresmentioning
confidence: 75%
“…At autopsy, the frequency of primary cardiac tumours is estimated to be between 0.001 and 0.030% [1,2]. Among these, about 75% are benign, mainly myxomas.…”
Section: Introductionmentioning
confidence: 99%